Wound healing promotion by poly(vinyl alcohol)/chitosan electrospun nanofibrous scaffold loaded with Achillea wilhelmsii extract - Omid Tavallaei; Mahtab Doostan; Kamyar Khoshnevisan; Ali Tahmasebi; Hassan Maleki (Nanomedicine Journal)
Objective(s): Natural component-included scaffolds can provide numerous benefits for skin healing and tissue regeneration. Nanofibers (NFs) with intricately intertwined three-dimensional structures afford an exclusive matrix for delivering therapeutics. This research assessed nanofibrous scaffolds loaded with Achillea wilhelmsii extract (5-15 wt%) for skin tissue engineering. Materials and Methods: A. wilhelmsii-loaded scaffolds, composed of poly(vinyl alcohol) (PVA) and chitosan (CS), were fabricated by the electrospinning process. Subsequently, the physicochemical properties of the scaffolds were evaluated through relevant analyses. The antioxidant activity and degradation rate of the scaffolds were also determined. Cell viability and scratch assays on dermal fibroblasts were conducted to assess proliferation and migration activities.  Results: Electron micrographs revealed interconnected fibers with a nano-scale diameter (> 400 nm) and uniform morphology. Additionally, the intact presence of A. wilhelmsii extract in the polymeric matrix was confirmed without any undesirable interactions. The proposed scaffolds verified favorable mechanical properties, a hydrophilic nature, high volume porosity (>90%), and water absorption capability (<500%). Besides, the findings demonstrated the remarkable radical scavenging ability of A. wilhelmsii extract in the nanofibrous scaffolds, along with controlled degradation kinetics over 72 h. The viability assay proved that the A. wilhelmsii-loaded scaffolds not only exhibited no cytotoxicity but also improved cell proliferation. The scaffolds also significantly accelerated fibroblast migration and complete closure of scratched areas. Conclusion: At last, the obtained results revealed that A. wilhelmsii-loaded PVA/CS NFs can be applied as a potential scaffold for skin regeneration and wound healing promotion.